2011
DOI: 10.1161/circulationaha.111.039008
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-24 Regulates Vascularity After Myocardial Infarction

Abstract: Background-Myocardial infarction leads to cardiac remodeling and development of heart failure. Insufficient myocardial capillary density after myocardial infarction has been identified as a critical event in this process, although the underlying mechanisms of cardiac angiogenesis are mechanistically not well understood. Methods and Results-Here, we show that the small noncoding RNA microRNA-24 (miR-24) is enriched in cardiac endothelial cells and considerably upregulated after cardiac ischemia. MiR-24 induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
330
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 364 publications
(350 citation statements)
references
References 53 publications
19
330
1
Order By: Relevance
“…In zebrafish, miR-451 targets gata-2 during erythroid maturation (31). miR-24 was also shown to target GATA-2 in human endothelial cells (32). Although we observed that miR-24 is up-regulated upon SON knockdown in both K562 cells and EML cells, overexpression of miR-24 did not target the 3Ј-UTR of GATA-2 in hematopoietic cells (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…In zebrafish, miR-451 targets gata-2 during erythroid maturation (31). miR-24 was also shown to target GATA-2 in human endothelial cells (32). Although we observed that miR-24 is up-regulated upon SON knockdown in both K562 cells and EML cells, overexpression of miR-24 did not target the 3Ј-UTR of GATA-2 in hematopoietic cells (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Many of these miRNAs inhibit angiogenesis by suppressing proliferation and migration of endothelial cells, such as miR-21 by targeting proliferators-activated receptor-alpha (PPAR-α) and RhoB [27]; miR-200b by down-regulating Ets-1, VEGF, VEGFR-2 and GATA2 [28]; miR-92a by suppressing integrin subunit a5 [29]; and miR-221/222 by negatively regulating the expression of c-kit [30]. Moreover, in addition to suppressing angiogenesis by regulating GATA2, miR-24 also induces apoptosis by targeting p21-activating kinase 4 (PAK4) [31]. Similarly, miR-34a is significant in promoting senescence of endothelial cells, while it impedes angiogenesis by suppressing SIRT1 [32].…”
Section: Mirnas Regulate Behaviors Of Vascular Endothelial Cellsmentioning
confidence: 99%
“…Growing evidence shows that miRNAs are extensively involved in the pathogenesis of heart diseases (15), including cardiac hypertrophy (30), cardiac fibrosis (36), arrhythmia (43), heart failure (33), and MI (16,27). The miR-30 family, including miR-30a, miR-30b, miR-30c, miR-30d, and miR-30e, has been shown to alter cell proliferation, differentiation (37), migration, and invasion (6) in various carcinomas.…”
Section: Introductionmentioning
confidence: 99%